The changing landscape: ecosystem responses to urbanization and pollution across climatic and societal gradients. Issue 5 (1st June 2008) - Grimm, Nancy B; Foster, David; Groffman, Peter; Grove, J Morgan; Hopkinson, Charles S; Nadelhoffer, Knute J; Pataki, Diane E; Peters, Debra PC
Abstract : Urbanization, an important driver of climate change and pollution, alters both biotic and abiotic ecosystem properties within, surrounding, and even at great distances from urban areas. As a result, research challenges and environmental problems must be tackled at local, regional, and global scales. Ecosystem responses to land change are complex and interacting, occurring on all spatial and temporal scales as a consequence of connectivity of resources, energy, and information among social, physical, and biological systems. We propose six hypotheses about local to continental effects of urbanization and pollution, and an operational research approach to test them. This approach focuses on analysis of "megapolitan" areas that have emerged across North America, but also includes diverse wildland‐to‐urban gradients and spatially continuous coverage of land change. Concerted and coordinated monitoring of land change and accompanying ecosystem responses, coupled with simulation models, will permit robust forecasts of how land change and human settlement patterns will alter ecosystem services and resource utilization across the North American continent. This, in turn, can be applied globally.